PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG, PERPUTARAN PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP LABA BERSIH PADA PT. ASTRA HONDA MOTOR MEDAN PERIODE 2013 - 2017 - LUVITA .; NOVIA .; SALEH SITOMPUL; NIRWANA DEWI HARAHAP (LP2MTBM MAKARIOZ, 2019)
The purpose of this study is to determine and analyze the Influence of working capital Turnover, accounts receivableTurnover, inventory Turnover and sales Growth To net Profit At PT Astra Honda Motor Medan. The method used in thisresearch is descriptive analysis method with a way to describe or depict the data that has been collected as is withoutintending to make a conclusion that applies to general or generalised. Methods of data analysis used was Multiple LinearRegression using SPSS software. The research result show the working capital turnover, accounts receivable turnover,inventory turnover and sales growth against net profit simultaneously it has some positive effects and significant impact onnet profit. In the coefficients determination value adjusted r2 who receive is 17,1 % it means variation variable working capitalturnover, accounts receivable turnover, inventory turnover and sales growth can explain the effect on net income of 17.1%while the remaining 82.9% is a variation of other variables not explained in this study. Working capital turnover, accountsreceivable Turnover and sales Growth partially has no effect and is not significant to net Income. This shows the workingcapital Turnover, accounts receivable Turnover, and sales Growth has no effect in theory and in real increase in net Income.Inventory turnover is partially positive and significant effect on net Income. This shows the inventory turnover effect siginfikanin improving the net Income of PT. Astra Honda Motor Field Period 2013-2017.